Trotting down the memory lane - Lohani, Ishwar (Journal of Society of Surgeons of Nepal, 2017)
Born on 1962 at Kamaladi, Kathmandu, Prof Ishwar Lohani completed School Leaving Certificate from St. Xavier’s School. Lalitpur. followed by Senior Cambridge ‘O’ Level from Cambridge University 1980 and Proficiency Certificate Level from Amrit Science Campus. 1984. He did B. Muse. (Sangeet Prabhakar) in Tabala from Kalanidhi Sangit Manavidyalaya under Prayag Sangit Samiti, Allahabad. 1983. He completed M.B.B.S Degree from Madurai Medical College under Madurai Kamaraj University, Madurai, Tamilnadu, India. 1991 and MS General Surgery from PGIMER, Chandigarh, India. 1994. After completion of M.Ch. Plastic Surgery from PGIMER, Chandigarh, India in 1997, he worked initially as a Senior Medical Officer for few months and later as Senior Resident in the Dept. of Surgery, Chandigarh Medical College. He completed fellowship in Plastic Surgery as PSEF International fellow from University of Southern California, Los Angeles and California Pacific Medical Center, San Francisco May 2001 to Feb 2002 under Dr. Randy Sherman and Dr. Bryant Toth. He later did fellowship in Plastic Surgery through the Scottish Foundation for Surgery in Nepal at St. John’s Hospital, Livingstone and Canniesburn Hospital Glasgow, England from Jan 17, 2003 to Feb 28, 2003 under Dr. Auf Quaba and Dr. David Soutar. Presently working as Professor and Head of Department, Dept. of Plastic Surgery and Burns at the T.U. Teaching Hospital, Maharajgunj, Kathmandu, Nepal. He has been involved in the training of MBBS, MS (General Surgery) and MCh Plastic surgery graduates at the Maharajgung Medical Campus. He served as the President of the International College of Surgeons (ICS) Nepal Section; General Secretary of Association of Plastic Surgeons of Nepal (APSON). He has been member of Society of Surgeons of Nepal since 1996 and has contributed a lot in the activities of the society. He has presented in numerous National and International conferences and has numerous publications in international and national journals as well. He served as the Chief Editor of the Journal of Society of Surgeons of Nepal 2008 – 2014.